A THESAURUS OF MODERN CHINESE (TMC) FOR CHINESE LANGUAGE LEARNER IN VOCABULARY LEARNING (TESAURUS CHINA MODERN (TCM) UNTUK PEMELAJAR BAHASA CHINA DALAM PEMELAJARAN KOSAKATA) - Fransiska Wiratikusuma (Balai Bahasa Jawa Barat, 2021)
A Thesaurus of Modern Chinese 《现代汉语分类词典》(TMC) can guide learners in searching a word by its classification words. The classification of parts of speech in this thesaurus is one of the practical uses for Chinese learners to know the function of words. Difference on Chinese as foreign language which concern with words of spoken language and Chinese as native language which concern with words of written language is one of the difficulties for Indonesian Chinese learner in using TMC. Although TMC is a thesaurus for mother language learner, it is not only collecting words by frequency like reference books of Chinese as foreign language, but it can also be a fruitful “word bank”reference book for advanced learners because it emphasizes the Chinese semantic and cultural terms in collecting and classifying words. By using TMC, we can find the words that are related to things that native speakers use, the words that can reflect Chinese culture, society and habits with the classification of words.